P Pemanfaatan Media Sosial Tiktok Sebagai Strategi Pemasaran Bisnis Kuliner Di Barru - Dinif Rasyid (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2023)
Empangku Restaurant in Mallusetasi District, Barru Regency. The number of customers, good facilities and quality of employees is not directly proportional to the financial performance of the business. So what can be formulated in this research is the marketing strategy for the Empangku Restaurant business in Mallusetasi District, Barru Regency. The aim of this research is to find out the marketing strategy for Empangku Restaurant in Mallusetasi District, Barru Regency. Culinary Business Marketing Strategy Using Tiktok Social Media (Case Study at Rumah Empangku). This type of research uses primary data and secondary data using a qualitative research design. The number of informants in this research was 15 people (1 owner, 4 employees and 10 visitors). The sample will be obtained using purposive sampling technique. Data collection techniques can be carried out by means of interviews, and observations, and a combination of the three, directly from respondents selected as samples, which includes the respondent's identity data. Based on the results obtained using qualitative analysis, it can be concluded in this research that the reason why Rumah Empangku's marketing strategy shifted from conventional methods to TikTok marketing is, because of technological advances, consumers are more inclined to use TikTok social media and to use social media marketing, especially TikTok. can further reduce costs in marketing financing and have a positive impact on the progress of Rumah Empangku, finally the role of the place variable in the marketing mix can make visitors come back to Rumah Empangku because Rumah Empangku provides an attractive atmosphere for consumers and the price is also appropriate. consumer pockets. This place, which according to researchers is very strategic because it is on the side of the road, with advances in technology and promotional strategies for Rumah Empangku, can immediately attract consumers.